Macroprudential transparency and price stability in emerging and developing countries - Emna Trabelsi (Journal of Central Banking Theory and Practice, 2022)
One of the focuses of recent literature has been the macroeconomic effects of macroprudential policy instruments. The innovation of this paper is that it studies the effects of transparent macro-prudential policies on price stability. The results presented herein provide the first empirical evidence that macroprudential transparency can aid to achieve stable inflation in emerging and developing countries. The effect is necessarily transmitted through reduced occurrence of banking crises. We also record a particular advantage of macroprudential transparency for non-inflation targeting countries. Overall, the results are robust to the use of two proxies of price stability.
Keywords: C33; E31; E52; E58; 330; macroprudential transparency; price stability; banking crisis; dynamic panel; mediation; bootstrapping